Increasing Employee Engagement by Assessment of Their Satisfaction - Holá, Jana; Špačková, Iva; Záhorová, Věra (Technická univerzita v Liberci, 2017)
Assessment of satisfaction and finding incentives for greater engagement of employees should be a standard tool of human resources management. In healthcare organizations, satisfied and engaged employees are a guarantee of quality health care. The way leads through satisfied employees to satisfied patients, who are the main subject of interest of medical facilities. Organizational culture has a significant influence on the employee satisfaction and engagement. It is a task for the management to create a healthy organizational culture, conditions for effective communication, to increase employee loyalty and to motivate employees to achieve good results. This paper presents a part of the results of the satisfaction survey in a selected acute care hospital in the Czech Republic. The survey included 1 564 respondents. Data were obtained using anonymous questionnaires. These questionnaires contained six domains of stimulants involved in the creation of job satisfaction. The paper provides information on the average value of individual domain ratings and about relations between all domains expressed by Spearman´s correlation coefficient. Respondents evaluated the best domain - the level of the formal setting of work (average rating 1.77), the worst domain - the level of belonging to the organization (average rating 2.62). This domain has a strong relation with the domain the level of self-realization, satisfaction with personal and professional development (correlation coefficient 0.70) and the domain - the level of engagement and conditions of potential for innovation and cooperation (correlation coefficient 0.61).
Zvyšování angažovanosti zaměstnanců hodnocením jejich spokojenosti
Keywords: Engagement; health care; organization culture; satisfaction; Angažovanost; zdravotní péče; spokojenost